Prevalence and antimicrobial resistance pattern of staphylococcus aureus in the hospital waste water and adjacent community water in Dhaka city - Lira, Silvia Alam; Anzum, Ramisa (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Microbiology, 2023.